2000
DOI: 10.1046/j.1365-2516.2000.00400.x
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant FVIIa (NovoSeven) continuous infusion and total hip replacement in patients with haemophilia and high titre of inhibitors to FVIII: experience of two cases

Abstract: In this report we describe our experience of total hip replacement in two patients with severe haemophilia A and high titres of inhibitors to FVIII. We used rFVIIa replacement therapy by continuous infusion to perform the surgery. The total amount of rFVIIa used in these two patients was very similar but the manner of administration was quite different. In our experience, it is an advantage to use a higher dose for shorter periods than a lower dose for a longer treatment period. Tranexamic acid by continuous i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 7 publications
0
28
0
Order By: Relevance
“…Issues related to the use of rFVIIa are the short halflife that requires frequent and repeated infusions particularly for surgery and the extremely high cost of a course of treatment. Continuous infusion of rFVIIa 16.5-50.0 lg kg h )1 [88][89][90][91][92][93][94][95][96], after administration of a bolus dose, has been shown to be effective with a 30% cost reduction [81,85,86], but no precise guidelines are available for its use by continuous infusion, a regimen that is not licensed at the moment.…”
Section: Treatment Of Bleeding and Prophylaxismentioning
confidence: 99%
“…Issues related to the use of rFVIIa are the short halflife that requires frequent and repeated infusions particularly for surgery and the extremely high cost of a course of treatment. Continuous infusion of rFVIIa 16.5-50.0 lg kg h )1 [88][89][90][91][92][93][94][95][96], after administration of a bolus dose, has been shown to be effective with a 30% cost reduction [81,85,86], but no precise guidelines are available for its use by continuous infusion, a regimen that is not licensed at the moment.…”
Section: Treatment Of Bleeding and Prophylaxismentioning
confidence: 99%
“…Although the same surgical procedures would be equally appropriate for patients with and without inhibitors, it was not until haematologists accumulated experience with haemostatically effective FVIII bypassing agents, namely activated prothrombin complex concentrates (APCCs) and recombinant activated factor FVII (rFVIIa), that it became feasible to consider performing ‘elective’ surgery in haemophilia patients with inhibitors. As Hedner’s pioneering report of a knee synovectomy on an inhibitor patient with the use of rFVIIa in 1988 [5], numerous single‐case reports and case series have reported good to excellent haemostatic results in patients undergoing a wide variety of major and minor surgical procedures, both orthopaedic and non‐orthopaedic [6–16].…”
Section: Resultsmentioning
confidence: 99%
“…rFVIIa has been approved for the treatment of bleeding in haemophiliacs with inhibitors. Tagariello et al [30] have used rFVIIa during total hip replacement in two patients with haemophilia and high-titre inhibitors, and found that it to be effective. Therefore, the sites of activity are those in which it is needed, and the threat of DIC is considered to be minimal [7,29].…”
Section: Discussionmentioning
confidence: 99%